NAPHTHAQUINONES OF ALKANNA ORIENTALIS (L.) BOISS - Tawfik, Wafaa A.; Shams, Khaled A.; Abdel-Azim, Nahla S.; Hassan, Nahed M.; Ismail, Shams I. (African Journal of Traditional, Complementary and Alternative Medicines, 2006)
The roots of Alkanna orientalis (L.) Boiss yielded α- methyl-n-butyl alkannin (compound 1) and alkannin acetate (compound 2). The compounds were identified by UV, MS, 1H NMR and 13C NMR. Quantitative determination of α- methyl-n-butyl alkannin and alkannin acetate in Alkanna orientalis (L) Boiss roots was established by TLC densitometry.